TENDA BARAK PENGUNGSI BERTENAGA SURYA MULTIGUNA - FA Widiharsa; Nurhamdoko Bonifacius (University of Merdeka Malang, 2016)
Applications of integrated photovoltaic electrical energy promises 'clean and mean'. People considered 'clean' because there is no exhaust emissions or pollutants and is considered 'saving' because it does not require fuel. In the tropics, sunshine reaching Earth's surface. Sunlight is the source of electrical energy. Electrical energy is urgently needed in the refugee camps in remote areas (remote areas) and or a natural disaster. In such locations, providing electrical energy becomes a major problem. Generator sets are easy to use but the problem is the availability of fuel oil. Transportation of fuel to remote locations make the price of fuel becomes economically feasible. On the other hand, solar electric energy can be obtained free of charge at the site, without the distribution line and without transmission. The price of solar power is the price of the device alone, being free electricity. Solar power generation is to be constructed. Increased capacity is easy to do because only adds to the module unit. Methods of laboratory experiments conducted in outer space. Book study to identify the needs of a wide and electrical load of refugees activity. Experiments in the laboratory standardization of outdoor space to get daily energy output. It is also related to the need and the unit load. Experiments were also conducted to standardize the system, the test model of a solar power plant integrated multipurpose, build a prototype.